Maria Nordman : De Sculptura II : Stad/sculptuur. - Nordman, Maria; von Wiese, Stephan (Ostfildern-Ruit : Cantz Verlag, 1997)
In the course of her works Maria Nordman has brought the discussion constituting the meaning of art from the museum into the city streets. In the context of her working a work of art could be placed at any time and into any neighborhood of the city.
Book/Sculpture for use by two or more persons at a time
Conjuct to this book / sculpture: An exhibition made as a sculpture : Maria Nordman : Some early ongoing works, Museum Folkwang Essen, February 23 to April 20, 1997
Engels & Italiaans
boek
Keywords: Nordman, Maria